PENYULUHAN VIRTUAL TENTANG MANFAAT PIJAT BAYI TERHADAP TUMBUH KEMBANG KEPADA IBU YANG MEMILIKI BAYI USIA 6 BULAN -1 TAHUN - Purti Ayu Yessy Ariescha; Peny Ariani; Mutiara Dwi Yanti; Andayani Boang Manalu; Tetty Junita Purba; Gf Gustina Siregar (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
Touch therapy or massage is a complex form of therapy which involves physical and emotional touch. Massage can be applied to all ages, including babies. Baby massage is a form of stimulation in the form of touch aimed at the baby's growth and development. Baby massage can increase the quality and quantity of baby sleep so that it stimulates the hormone endorphins to reduce pain and will make the baby calm, ultimately reducing the frequency of baby crying. The problem that occurs is that many mothers do not understand what the benefits of baby massage are and how to do it. An alternative solution to the problem that can be done is by providing counseling which is done virtually during the Covid-19 pandemic. The service was carried out for mothers who have babies aged 6 months-1 year in the work area of ​​the Biru-Biru Puskesmas as many as 32 people. The community service implementation team provided counseling virtually for 2 days with prepared materials, after which measure the mother's knowledge before and after counseling. The results showed that the counseling went well, and there was an increase in the mother's knowledge about the benefits of baby massage for baby growth and development, and mothers were able to massage their babies to their respective babies.